A democratização da educação no município de Sarandi, Paraná: as diretrizes educacionais do governo do PT (2001-2008) - Araújo, José Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The struggle for the democratization of the educational management coincided with the fight of society for the redemocratization of the country, the end of 1970s. Consequently, with the end of the military regime, the principle of the democratic management of the public teaching was inscribed in the Federal Constitution of 1988, and later, in the LDBEN Law 9.493/96. Since then, the system of democratization in the educational management was inscribed in the pedagogic projects of the public educational institutions, and also in the election platforms of the political parties, including the PT (Workers‟ Party). This study analyzed the experience of the democratic management, in the city of Sarandi-PR. The research was developed in the period from 2001 to 2008, with the intention of verifying whether the elections of directors and school boards were constituted, at that moment, as political participation spaces, as well as spaces of the democratization of power relations. As specific objectives, we have situatinge the struggle of educators in favor of the democratization of the educational management, during the military regime (1964-1985); understanding the concept of education and the educational guidelines proposed by the Workers‟ Party; understanding the historical, social and political determinants that contributed to the achievement of the educational policy of the Workers‟ Party, in Sarandi; to analyzinge the educational policy developed in Sarandi, in the period from 2001 to 2008, and analyzinge the process of democratization of the educational management. The analysis materials were the educational management reports, the texts produced by the school communities, and the official documents of the municipality, produced in the period which deal with the democratization of the school management. The survey also included the application of a questionnaire for faculty and staff members who participated in the democratization...

A luta pela democratização da gestão da educação coincidiu com a luta da sociedade pela redemocratização do país nos anos finais da década de 1970. Em consequência, com o fim do regime militar, o princípio da gestão democrática do ensino público foi inscrito na Constituição Federal de 1988 e, posteriormente, na LDBEN Lei 9.493/96. A partir de então, o dispositivo da gestão democrática foi inscrito nos projetos pedagógicos das instituições de ensino públicas e, também, nas plataformas eleitorais dos partidos políticos, entre eles, o PT. Neste trabalho, analisamos a experiência de gestão democrática do município de Sarandi-Paraná. desenvolvida no período de 2001 a 2008, com a intenção de verificar se as eleições de diretores e os conselhos escolares se constituíram, naquele momento, como espaços de participação política e de democratização das relações de poder. Com os objetivos específicos, buscamos: situar a luta dos educadores em favor da democratização da gestão da educação no período do regime militar (1964-1985); compreender a concepção de educação e as diretrizes educacionais formuladas pelo Partido dos Trabalhadores; compreender os determinantes históricos, sociais e políticos que contribuíram para a realização da política educacional do Partido dos Trabalhadores no município de Sarandi-Pr.; analisar a política educacional desenvolvida no município de Sarandi-Pr., no período de 2001 a 2008 ; analisar o processo de democratização da gestão da educação. Os materiais utilizados para a análise foram os relatórios de gestão da educação, os textos produzidos pelas comunidades escolares e os documentos oficiais do município que tratam da democratização da gestão escolar produzidos nesse período. A pesquisa contou, também, com a aplicação de um questionário para os trabalhadores do ensino que participaram do processo de democratização. Defendemos que a política...
Keywords: Partido dos Trabalhadores (Brasil); Gestão democrática; Educação e Estado Parana 2001-2008; Education